Transnational Network and Information Flow in African Refugees and Undocumented Migrants’ International Migration Process - Eddy Bruno Esien (Yayasan Ilomata, 2022)
This paper analyses the role of information flow under transnational (social) networks to understand African refugees and undocumented migrants’ migration to Austria. Existing research pointed to the international refugee crisis with industrialised countries targeted border governance that has prompted the emergence of the transnational (social) network, which builds (kinship-based) connectivity and interchangeable acquaintances between migrants in host and country of origin to influence and facilitate migrants’ pre and post mobility process. However, the network often faces weak ties with exploitation and subjugation to human trafficking. Based on twenty qualitative problem-centred face-face interviews, data are collected and analysed with content analysis technique to fill in the gap. The findings indicate that pre-mobility guidance, directive, and legislative decoder regulatory tools influence transnational networks with a lack of well-managed network that may impair pre and post-mobility processes to shape African refugees and undocumented migrant international migratory pathways in an information flow setting. This study demonstrated actor-based network-driven advocacy governance. The outcome points to the strategic mobilization of collective information to resource vulnerable people and refugees or undocumented migrants to meet their needs. This is relevant to collective action in contemporary neoliberal society targeting freedom and movements that may not only constrain ethnic minority group mobility, but the universal human rights principles, public policy learning process, informal institution collaborative actions, and democratic values in times of crisis-related super-diversity societies.